GENDER DIFFERENCES AND PREDICTORS OF INCRASED CORONARY CALCIUM SCORE AND MYOCARDIAL ISCHEMIA IN DIABETES TYPE 2 PATIENTS - Mitevska, Irena; Zdravkovska, Maja; Stoilovska, Bojana; Manevska, Nevena; Mileva, Magdalena; Vavlukis, Marija (Journal of Morphological Sciences, 2021)
We wanted to assess prevalence, predictors and gender difference of coronary calcium score (CCS) and myocardial ischemia in diabetes type 2 patients.  We have evaluated 145 patients (58 male and 87 females, age 63+/-9), who underwent single-photon emission computed tomography myocardial perfusion imaging computer tomography (SPECT/CT) for assessment of myocardial ischemia and coronary atherosclerosis burden. Forward logistic regression analysis was used to assess predictive parameters for myocardial ischemia and increased CAC. Gender differences between myocardial perfusion and CCS findings were analyzed. SPECT results were normal in 102 patients (70%). Mild ischemia was noted in 16 patients (37%), moderate ischemia in 9 patients (20%), severe ischemia in 10 patients (23%), and fixed defects in 8 patients (18%). CCS >0 Agatston Units (AU) was found in 69 patients (62.7%), with average CAC 198+/-45 in male and 98+/33AU in female patients. 24 patients (34%) had moderate CCS (100â€“399 AU) and 19 patients (27.5%) had severe CCS (401â€“1000 AU). Multivariate regression analysis showed independent predictors for CCS (>0AU) age (â©¾65 years) (odds ratio (OR): 1.074, p = 0.028), smoking (OR: 1.81, p = 0.048) and male gender (OR: 1.43, p = 0.051). We found stress-induced ECG changes, CCS>400AU and diabetes type 2 over 10 years to be independent predictors of myocardial ischemia in the model that included CCS. CCS was increased predominantly in male and myocardial ischemia was more prevalent in female patients. SPECT/CT imaging enable assessment of anatomic and functional aspects of CAD and optimize treatment in diabetes type 2 patients. Keywords : Myocardial perfusion imaging, coronary calcium score, type 2 diabetes, coronary artery disease https://doi.org/10.55302/JMS2141083m